Design and Study on Dynamic Measuring System for Field Surface Roughness - Lv Xiao-Rong; Liu Ming-Dan; Lv Xiao-Lian (Institute of Advanced Engineering and Science, 2014)
Explore the adaptability and relationship of planter to field surface roughness. Through field test of the designed dynamic testing system of field surface roughness, the two types of field surface roughness were detected on the original field surface roughness formed by the working rotary and the field surface roughness formed after planters work. The transfer functions of the system were established, and the dynamic characteristics of the system were analyzed. The results show that, the system is a linear one with the typical first order feature. The dynamic characteristics of the systems such as response speed, frequency bandwidth and thickness of covering soil and other performance indicators are able to meet the requirements of agricultural technology.